THE CULTURE OF CATFISH (Clarias sp.) FRY IN THE PEAT POND BASED ON PINEAPPLE (Ananas comosus L) TUBER AND BANANA (Musa sp.) STEM CRUDE EXTRACT WITH COMMERCIAL PROBIOTIC MIX - Ricky Djauhari; Noor Syarifuddin Yusuf; Shinta Sylvia Monalisa; Muhammad Noor Yasin; Maryani Maryani; Mohamad Rozik; Muhammad Fazri; Petrus Senas; Yanetri Asi Nion; Aris Toteles; Riamona Sadelman Tulis; Fatma Sarie; Lamria Simamora; Tatik Zulaika; Dewi Klarita Furtuna (Jurnal Perikanan Unram, 2024)
One of the obstacles in cultivating catfish (Clarias sp.) is low feed efficiency. Therefore, a breakthrough is needed in catfish cultivation to increase the efficiency of feed utilization which will lead to increased production and profits in catfish cultivation businesses. This study aims to evaluate the effect of supplementation with crude extracts of pineapple tubers and banana stems as well as commercial probiotic mixes on the growth performance of catfish in flooded peat soil ponds. This study consisted of four treatments, namely control (A), 6% crude extract of pineapple weevil, 2% crude extract of banana stem, and 0.2% commercial probiotic mix (B), 6% crude extract of pineapple weevil, extract 2% banana stem crude, and 0.4% commercial probiotic mix (C), and 6% dose of pineapple tuber crude extract, 2% banana stem crude extract, and 0.6% commercial probiotic mix (D) are mixed into the feed with repeated three times. Fish with an average initial weight of 1.5 g were randomly stocked in 12 hapa measuring 1 x 1 x 1 m3 installed in earthen ponds at a density of 40 fish/hapa. Fish were given the test feed ad satiation twice a day for 28 days. Supplementation with a 6% dose of pineapple tuber crude extract, 2% banana stem crude extract, and 0.4% commercial probiotic mix (treatment C) showed the best results on catfish growth performance parameters, namely the least amount of feed consumption, but still had biomass performance. harvest and daily weight growth were the same as controls.